Alternating electric field-induced ion current rectification and electroosmotic pump in ultranarrow charged carbon nanocones. Issue 44 (31st October 2018) - Li, Wen; Wang, Wensen; Hou, Quangang; Yan, Youguo; Dai, Caili; Zhang, Jun
Abstract : Molecular dynamics simulations were performed to study a symmetrical sinusoidal electric field-induced electroosmotic pump in ultranarrow charged carbon nanocone (CNC) channels. Abstract : Pumping fluid in ultranarrow (sub-2 nm) synthetic channels, analogous to protein channels, has widespread applications in nanofluidic devices, molecular separation, and related fields. In this work, molecular dynamics simulations were performed to study a symmetrical sinusoidal electric field-induced electroosmotic pump in ultranarrow charged carbon nanocone (CNC) channels. The results show that the CNC channels could rectify the ion current because of the different ion flow rates in the positive and negative half circles of the sinusoidal electric field. Electroosmotic flow (EOF) rectification yielded by the ion current rectification is also revealed, and net water flow from the base to the tip of the CNC channels is observed. The simulations also show that the preferential ion current conduction direction in the ultranarrow CNC channels (from base to tip) is opposite to that in conical nanochannels with tip diameters larger than 5 nm (from tip to base). However, the preferential EOF direction is the same as that of large conical nanochannels (from base to tip). We also investigated the influences of ion concentration and the amplitudes and periods of the sinusoidal electric field on the EOF pump. The results show that high ion concentration, large amplitudes, and long periods are desired for high EOF pumping efficiency. Finally, through comparison with a constant electric field and a pressure-induced water pump, we prove that the EOF pump under an alternating electric field has a higher pump efficiency. The approach outlined in this work provides a general scheme for pumping fluid in ultranarrow charged conical nanochannels.